Research on the Mechanism of Involution from the Perspective of Supermodular Games - Xiaofeng, Zhang (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2025)
By constructing two-player and multi-player game models and incorporating strategic complementarity analysis from supermodular games, this paper reveals how individuals increase their effort levels to cope with competition, leading to overall system resource waste. On this basis, the paper further analyzes how different game parameters affect equilibrium stability, showing how involution gradually forms through dynamic game evolution, and validates the model through simulation experiments. The novelty of this paper lies in the first-time application of supermodular games to the study of involution, providing a new theoretical perspective and a detailed exploration of the formation mechanism of involution through multi-level game models and simulation experiments. Furthermore, this paper proposes policy recommendations to address involution, emphasizing the optimization of institutional design and adjustments to incentive mechanisms to break the involution trap.